The historical-ideological roots of the Zionist-Israeli settler colonialism and ethnic cleansing of Palestine - Zhumatay, G.B.; Yskak, A. (Journal of Oriental Studies, 2024)
The paper investigates the ideological and historical roots of the Zionist-Israeli policy and practice of ethnic cleansing of the indigenous Palestinians to build an exclusivist ethnocratic Jewish state in Palestine. The ongoing Israeli military invasion of Gaza, since October 7th, 2023, shows that the Jewish state of Israel and its political leaders do not conceal their genocidal intent towards the Palestinian population of both Gaza and the West Bank. The intention of Israel in its war against Gaza is to empty or purify this area of its Palestinian residents and replace them with Jewish settlers, building and expanding Israeli settlements in Gaza like Israel has been doing in the West Bank since 1967. Therefore, our study seeks to answer the following question: Why from its inception has ethnic cleansing of the indigenous Palestinians been a consistent and coherent goal and policy of Zionism? To answer this question, we need to put the so-called Israeli-Palestinian conflict in historical context by critically examining the historical roots and ideological foundations of the Zionist settler colonial enterprise aimed at displacing Palestinians to make room for the Jewish state of Israel. Employing the critical discourse analysis of Michel Foucault and the concept of cultural reproduction of Pierre Bourdieu we will critically analyze discourses about population transfer promoted by early Zionist leaders in the pre-state period. In addition, we deploy the concepts of settler colonialism to understand colonial and expansionist character of the Zionist movement and the state of Israel. Having critically analyzed relevant literature and closely examined historical and political discourses underpinning Zionism, we have revealed the continuities of the Zionist strategy of the elimination and erasure of the indigenous Palestinian people and building an exclusivist ethnocratic Jewish state in Palestine. From its inception the Zionist movement and ideology has been colonial and eliminationist in its essence aimed at the removal of the indigenous population and replacement of Palestinians with the exogenous colonial settler population from Europe. Keywords: Palestine, Israel, Zionism, settler colonialism, ethnic cleansing, Palestinians, Arabs, Jews